THE PROGRESSIVITY OF PHYSICAL AND SOCIAL DEVELOPMENT OF ISLAMIST GROUPS IN BANDUNG CITY: A STUDY ON THE EVALUATION OF THE LEADERSHIP OF THE PARTAI KEADILAN SEJAHTERA (PKS) FOR THE 2018-2023 PERIOD - Adiwilaga, Rendy; Hasanah, Dera Izhar (KOMITMEN: Jurnal Ilmiah Manajemen, 2024)
As a party that dominates the government in Bandung City, from the executive aspect (before Oded M. Danial died in 2021) to the legislature, the Partai Keadilan Sejahtera (PKS) is actually a public â€œhopeâ€ for how Islamist groups can successfully manage a region. After several regions such as Riau and Depok experienced stagnation, Bandung City became the spotlight on how PKS built the region with its vision as an Islamic party. The research focuses on the Islamist ideology approach applied in development policies, more specifically in the physical development sector, social development, and civil society involvement and response. Using qualitative methods based on primary and secondary data, this article shows that although some initiatives have been executed, there is also some stagnation that requires strategic improvement. PKS's experienced focus on empowering women and children has not brought significant changes at the smallest level such as the urban village. Even PKS failed in providing creative space for youth. Meanwhile, in the aspect of physical development, the leadership of the mayor carried by PKS tends to favor the construction of flyovers, which have not fully answered people's concerns in overcoming congestion and the need for public transportation.